High incidence of early onset preeclampsia is probably the rule and not the exception worldwide. 20th anniversary of the reunion workshop. A summary. (June 2019) - Robillard, Pierre-Yves; Dekker, Gustaaf; Chaouat, Gérard; Elliot, Michael G.; Scioscia, Marco
Abstract: The 11th workshop on Immunology of preeclampsia in Reunion 2018 celebrated its 20th candle In this paper we try to summarize the main tracks of reflections during these two decades. First, of course, the advances in immunology of reproduction in the field of preeclampsia, which was poorly developed 2 decades ago when we first started in 1998. But, this workshop has not been dedicated only to immunology. Second, one of the main reflections has always been, workshop after workshop: "why does preeclampsia exists in humans?" in an evolutionary view, as we have no established natural animal models in the other some 4500 other mammal species. Third, besides the reflections on the biological plausibility of preeclampsia-disease-of-first-pregnancies-at-a-level-of-a-couple (primipaternity rather than primigravidity), i.e. immunology, paternal-maternal conflict, we had to face an apparent conundrum: the human species should have disappeared (almost 40–50% incidence of hypertensive disorders of pregnancy in couples conceiving within the first 4 months of sexual cohabitation). We report then the dialogues we were obliged to have with zoologists who themselves had no clues on our apparent "extravagant sexuality" and strange reproduction (ridiculous low fertility rate of the human female: 25%). Fourth, debates on the main difference between early onset ("rather immunological") and late onset PE ("rather maternal vascular predispositions"). Further, the debate of why high income countries report 90% of their PE being LOP, while other countries describe epidemiologically very high incidences of EOP. Finally, and always present at all workshops, the physiopathology of the reversible systemic maternal vascular inflammation.